Sistem Pendukung Keputusan Pemilihan Dosen Terbaik dengan menggunakan Metode TOPSIS (Studi Kasus: STMIK Pelita Nusantara Medan) - Simanjorang, R. Mahdalena (MEANS (Media Informasi Analisa dan Sistem), 2019)
The decision support system for the best lecturer selection has been made in this study so that it can be recommended to the foundation so that it is efficient compared to the use of the old system. In determining the lecturer at STMIK Pelita Nusantara, the method used is the TOPSIS method using criteria that will be determined by the Foundation. The selection of lecturers at STMIK Pelita Nusantara is determined by several criteria, namely, attendance, teaching, service, research and neatness. The Topsis method is very suitable because the concept is practical. The output in this system is the calculation value of lecturer selection using the TOPSIS method and the ranking of lecturers at STMIK Pelita Nusantara